THE ANALYSIS OF CHARACTERS IN THE NOVELS OF LIFE AND THE SOUND AND THE FURY: A COMPARATIVE ANALYSIS - Orifjonova Sarvinozkhon Azimjon qizi,R.Tillayeva (International Journal of Literature and Language Studies, 2026)
This article provides a comparative analysis of the characters in O‘tkir Hoshimov’s novel